Model Intrapreneurship Behavior, Transformational Leadership and Organizational Culture in Private University - Rojuaniah; Hendrani, Ai; Gumay, Barika; S. Brahmana, Sunardi (International Journal of Psychosocial Rehabilitation, 2020)
In order to develop an organization needs organizational culture and the leader who could be an inspiration and motivate the employees to become more independent, creative and innovative. The purpose of these studies intended to investigate the effects of organizational culture and leadership on intrapreneurship behavior in organizations. The design and methodology approach of this study is quantitative research. Objects and respondents in this research are private university lecturers. Data collected using questionnaires and direct interview with selected respondents. Data were analyzed descriptively and verificatively by using SEM (Structural Equation Model) analysis.The results of these studies founded that the dimensions of transformational leadership consisted of : inspirational motivations, intelectual stimulations, individual considerations and idealized influences has a positive and significant on lecturer intrapreneurship behavior. The dimension of organizational culture, both of the external focus (adaptability and mission) and internal focus (involvement and consistency) has a positive effect and significant on the employee’s intrapreneurship behavior. a strong organizational culture with the support of transformational leadership will encourage the creation of independent, proactive, creative and innovative behaviour of the lecturer